Effectiveness of Language Games (Guessing Pictures and Matching Words) on Speaking Skills - Rose Kumalawati; Martha Catherine (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2025)
This study aims to determine the effectiveness of language games (guessing pictures and arranging words) against maharah kalam at MADIN Al Falah Kesamben Jombang. Language games can affect the teaching of speaking skills. Because it covers the basics such as effectiveness, ideas and innovative for students. This research is quantitative research. Methods of data collection using observation, interviews, and documentation. The data analysis method used descriptive analytic method. The population of this research is first grade students. The sample in this study were all students of MADIN Al Falah Kesamben Jombang, totaling 24 students. Methods of data collection by observation, tests, documentation and questionnaires. The data analysis method used validity test, normality test, reliability test and ANOVA test. The results of the study: 1) The picture guessing language game was effective against maharah kalam at MADIN Al Falah Kesamben Jombang. The results of data analysis showed that the significant value of the picture guessing variable was 0.000 < 0.05. 2) The language game composes words effectively against maharah kalam at MADIN Al Falah Kesamben Jombang. The results of data analysis showed that the significant value of the word composing variable was 0.001 < 0.05. 3) The language game of guessing pictures and arranging words is effective against maharah kalam at MADIN Al Falah Kesamben Jombang. The results of data analysis show that the value of fcount is 4.255 > fTable 3.01. value (Sig.) 0.0003 < 0.05.